Pendidikan Seks pada Anak Usia Dini di Taman Kanak-Kanak (TK) Islam Kota Yogyakarta - Zubaedah, Siti (AL-ATHFAL : JURNAL PENDIDIKAN ANAK, 2016)
Sex education for young children is one of the most important part of education that should be conveyed to children as early as possible. This is because in order to avoid behaviors or treatment deviate either from the children themselves and from others. By using the phenomenological approach and methods of non-participation observation, this research seeks to uncover portrait sex education to early childhood in eleven TK Islam in Yogyakarta. One of the results of this study states that sex education in kindergarten eleven Islam in Yogyakarta is very good because the programs trying to combine sex education in general by religious moral values.